Novel Two-Component Systems Implied in Antibiotic Production in Streptomyces coelicolor - Yepes, Ana; Rico, Sergio; Rodríguez-García, Antonio; Santamaría, Ramón I.; Díaz, Margarita (PLOS ONE, 2011)
The abundance of two-component systems (TCSs) in Streptomyces coelicolor A3(2) genome indicates their importance in the physiology of this soil bacteria. Currently, several TCSs have been related to antibiotic regulation, and the purpose in this study was the characterization of five TCSs, selected by sequence homology with the well-known absA1A2 system, that could also be associated with this important process. Null mutants of the five TCSs were obtained and two mutants (ΔSCO1744/1745 and ΔSCO4596/4597/4598) showed significant differences in both antibiotic production and morphological differentiation, and have been renamed as abr (antibiotic regulator). No detectable changes in antibiotic production were found in the mutants in the systems that include the ORFs SCO3638/3639, SCO3640/3641 and SCO2165/2166 in any of the culture conditions assayed. The system SCO1744/1745 (AbrA1/A2) was involved in negative regulation of antibiotic production, and acted also as a negative regulator of the morphological differentiation. By contrast, the system SCO4596/4597/4598 (AbrC1/C2/C3), composed of two histidine kinases and one response regulator, had positive effects on both morphological development and antibiotic production. Microarray analyses of the ΔabrC1/C2/C3 and wild-type transcriptomes revealed downregulation of actII-ORF4 and cdaR genes, the actinorhodin and calcium-dependent antibiotic pathway-specific regulators respectively. These results demonstrated the involvement of these new two-component systems in antibiotic production and morphological differentiation by different approaches. One is a pleiotropic negative regulator: abrA1/A2. The other one is a positive regulator composed of three elements, two histidine kinases and one response regulator: abrC1/C2/C3.